A 420 steel plate for laminating PCB boards and a preparation method thereof
Through multi-stage cooling and multiple tempering treatment methods, combined with cold rolling and galvanizing treatment, the problems of irregular plate shape, unstable hardness and unstable warpage that exist during the quenching and tempering process of traditional 420 stainless steel are solved. , achieving the high hardness, toughness and flatness of the steel plate.
Patent Information
- Application Number
- CN202410567451.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-09
AI Technical Summary
During the quenching and tempering process, traditional 420 stainless steel has problems such as irregular plate shape, unstable hardness and unstable warping, resulting in poor product quality.
Adopt multi-stage cooling and multiple tempering treatment methods, including staged cooling after quenching, using a cooling method that combines salt bath, oil cooling and water cooling, and perform normalizing and secondary tempering treatment, combined with cold rolling and galvanizing treatment , and finally perform finished product annealing and plate shape correction.
It improves the hardness, toughness and flatness of the steel plate, ensures the high strength and high tensile strength of the plate, and solves the problems of unstable hardness and unstable warpage in traditional processes.
Smart Images

Figure BDA0004829784330000201 
Figure BDA0004829784330000211 
Figure BDA0004829784330000212
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of steel plates, and in particular to a 420 steel plate for laminating PCB boards and a preparation method thereof. Background Art
[0002] Multilayer laminated PCB circuit boards have obvious advantages in high-density wiring, electromagnetic interference suppression, short circuit risk reduction, size compression, signal integrity and transmission rate, and thermal management, and are suitable for electronic applications that require high performance and reliability. Multilayer laminated PCB is an electronic component substrate with multiple metal layers and insulation layers. During the manufacturing process, multiple single-layer PCBs are stacked together and laminated to form an integral structure. These layers can be connected by internal wires, providing higher circuit density and complexity.
[0003] The main features of 420 steel plate are as follows:
[0004] 1. High strength: The yield strength and tensile strength of 420 steel plate are much higher than those of general steel, which can improve the load-bearing capacity of the structure.
[0005] 2. High toughness: 420 steel plate has good impact toughness, can adapt to complex stress states, and improve the durability and safety of the structure.
[0006] 3. Good weldability: After being processed by appropriate welding process, 420 steel plate has good welding performance and can meet the design and processing requirements of the structure.
[0007] 4. Good corrosion resistance: 420 steel plate has good corrosion resistance and can be used in harsh environments.
[0008] 5. Good environmental performance: The production and manufacturing process of 420 steel plate is highly environmentally friendly and meets modern environmental protection requirements.
[0009] The heat treatment of 420 stainless steel used for laminated PCB boards is usually divided into two stages, quenching and tempering. In the quenching stage, the products made by traditional processes have irregular board shapes and excessive warpage, which brings many challenges to the subsequent leveling. In the tempering stage, the products made by traditional tempering processes have unstable hardness and unstable warpage, resulting in many products being scrapped. Summary of the invention
[0010] The purpose of the present invention is to provide a 420 steel plate for laminating PCB boards and a preparation method thereof, which has the advantages of large size (1300×1600mm), thin thickness (below 2mm), high hardness, excellent flatness (less than 0.5mm / m), large yield strength (1150-1500MPa), high tensile strength (1500-1800MPa), etc., and can be used to make PCB board pressing molding materials, mainly used in the PCB industry.
[0011] The technical solution of the present invention is achieved in this way:
[0012] The present invention provides a method for preparing a 420 steel plate for laminating a PCB board, comprising the following steps:
[0013] (1) The 420 steel plate is subjected to surface pickling treatment to remove the oxide film;
[0014] (2) quenching the steel plate treated in step (1) and then cooling it in stages;
[0015] (3) normalizing the steel plate treated in step (2), then performing a primary tempering treatment, naturally cooling to room temperature, then performing a secondary tempering treatment, and naturally cooling to room temperature;
[0016] (4) cold rolling the steel plate treated in step (3) to a thickness of less than 2 mm;
[0017] (5) immersing the steel plate treated in step (4) in a zinc solution, taking it out, cooling it to room temperature, drying it, immersing it in a protective film solution, heating it, taking it out, and drying it;
[0018] (6) performing final annealing on the steel plate treated in step (5);
[0019] (7) Correcting the shape of the steel plate treated in step (6) to obtain a 420 steel plate for laminating PCB boards.
[0020] As a further improvement of the present invention, the pickling acid in step (1) is 1-2 mol / L hydrochloric acid or sulfuric acid; the quenching temperature in step (2) is 900-910°C, the quenching holding time is 60-70 min, and the staged cooling is salt bath cooling between the quenching temperature and 650°C, oil cooling between 300°C and 650°C, and water cooling between 300°C and room temperature; the oil is silicone oil, and the salt is sodium chloride or potassium chloride.
[0021] As a further improvement of the present invention, the temperature of the normalizing treatment in step (3) is 890-900°C, and the holding time is 40-50min, the temperature of the primary tempering treatment is 550-600°C, and the holding time is 100-120min, the secondary tempering treatment is 670-690°C, and the time is 120-130min, and the heating rate of the tempering treatment is 3-5°C / min; the cold rolling in step (4) adopts a reduction rate of 50-60%, and the cold rolling temperature is 380-400°C.
[0022] As a further improvement of the present invention, the temperature of the zinc solution in step (5) is 454-459° C., and the protective film solution is a mixture of La / Sc oxide nanoparticles and cerium nitrate. 2 O 2 / silane hydrolyzate, the heating treatment temperature is 70-80°C, and the time is 0.5-1h.
[0023] As a further improvement of the present invention, the preparation method of the protective film liquid is as follows:
[0024] S1. Silane hydrolysis: dissolve the composite silane coupling agent in ethanol, add water, adjust the pH value of the solution, heat and stir to hydrolyze, and obtain a hydrolyzate;
[0025] S2. La and Sc doping: lanthanum nitrate and scandium nitrate are added to water, citric acid is added and stirred for reaction, the solvent is evaporated, calcined, and ball-milled to obtain La / Sc oxide nanoparticles;
[0026] S3. Ce deposition: adding the La / Sc oxide nanoparticles obtained in step S2 to the hydrolyzate obtained in step S1, stirring and mixing evenly, adding cerium nitrate, stirring and reacting to obtain a mixed solution;
[0027] S4. Preparation of protective film liquid: Add hydrogen peroxide to the mixed liquid obtained in step S3, stir and mix evenly to obtain a protective film liquid.
[0028] As a further improvement of the present invention, the composite silane coupling agent in step S1 is a mixture of KH580 and KH792, with a mass ratio of 3-5:7-9, the mass ratio of the composite silane coupling agent, ethanol, and water is 10-12:100-120:17-22, the pH value of the adjusted solution is 8-9, the temperature of the heated and stirred hydrolysis is 40-50°C, and the time is 1-3h; the mass ratio of lanthanum nitrate, scandium nitrate, and citric acid in step S2 is 4-6:2-3:7-10, the temperature of the stirred reaction is 35-45°C, the time is 20-40min, the temperature of the calcination is 400-500°C, the time is 1-3h, and the time of the ball milling is 2-4h.
[0029] As a further improvement of the present invention, the mass ratio of the La / Sc oxide nanoparticles, the hydrolyzate, and the cerium nitrate in step S3 is 3-5:100:4-6, and the stirring reaction time is 30-40 minutes; the mass ratio of the mixed solution and the hydrogen peroxide in step S4 is 100:10-15, and the concentration of the hydrogen peroxide is 25-30wt%.
[0030] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0031] S1. Silane hydrolysis: 10-12 parts by weight of a composite silane coupling agent is dissolved in 100-120 parts by weight of ethanol, 17-22 parts by weight of water are added, the pH value of the solution is adjusted to 8-9, heated to 40-50 ° C, stirred for hydrolysis for 1-3h to obtain a hydrolyzate;
[0032] The composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 3-5:7-9;
[0033] S2. La and Sc doping: 4-6 parts by weight of lanthanum nitrate and 2-3 parts by weight of scandium nitrate are added to 100 parts by weight of water, and 7-10 parts by weight of citric acid are added. The mixture is stirred at 35-45° C. for 20-40 min, the solvent is evaporated, and the mixture is calcined at 400-500° C. for 1-3 h, and ball-milled for 2-4 h to obtain La / Sc oxide nanoparticles.
[0034] S3. Ce deposition: add 3-5 parts by weight of La / Sc oxide nanoparticles obtained in step S2 to 100 parts by weight of the hydrolyzate obtained in step S1, stir and mix evenly, add 4-6 parts by weight of cerium nitrate, stir and react for 30-40 minutes to obtain a mixed solution;
[0035] S4. Preparation of protective film liquid: Add 10-15 parts by weight of 25-30wt% hydrogen peroxide to 100 parts by weight of the mixed solution obtained in step S3, stir and mix evenly to obtain a protective film liquid.
[0036] As a further improvement of the present invention, the finished product annealing in step (6) is carried out by continuous annealing in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled to be 770-800°C, and the burn-through time per millimeter is controlled to be 30-40s; the drawing reduction in the plate shape correction in step (7) is 0.1-0.15mm and the elongation is 0.3-0.5%.
[0037] The present invention further protects a 420 steel plate for laminating PCB boards obtained by the above-mentioned preparation method.
[0038] The present invention has the following beneficial effects:
[0039] The present invention solves the problems of high hardness and ultra-flatness of stainless steel by adjusting the heat treatment link of the steel plate. The deformation and heat treatment process are combined in the quenching stage to improve the comprehensive performance of the steel. The rapid cooling method is adjusted in the quenching stage, and the rapid cooling is divided into different stages. Different media and different times are used for cooling in each stage to carry out martensite (or bainite) transformation. Salt bath cooling is adopted when the temperature is high, which has the advantages of uniform temperature and high surface quality. Oil cooling is adopted at medium temperature, and the cooling speed is slow, which can improve the hardness and toughness of the steel to a certain extent. Water cooling is adopted in the low temperature stage, and the cooling speed is fast, which can make the structure of the steel finer and more uniform, so as to achieve the purpose of improving the hardness, toughness and other properties, thereby obtaining a steel plate material with high hardness and high toughness.
[0040] In the tempering stage, the present invention adopts a combination of secondary tempering and normalizing. The cooling speed of normalizing is faster than annealing but lower than quenching. The crystal grains of steel can be refined in slightly faster cooling, thereby improving the strength and toughness of steel, and the comprehensive mechanical properties can be greatly improved, and the cutting performance is also improved. The secondary tempering process can reduce or eliminate the internal stress generated during the quenching of the steel plate, prevent the deformation and cracking of the steel plate during use, and improve the toughness, strength and hardness of the steel; stabilize the structure so that the steel plate does not undergo structural transformation during use, thereby ensuring that the shape and size of the steel plate remain unchanged and the accuracy of the steel plate; and by adjusting the tempering temperature, the product is heated evenly at this stage, the austenite can be completely converted into martensite during the insulation stage, and the heat dissipation is faster during the natural cooling to room temperature stage, thereby improving the performance of the steel plate.
[0041] The present invention uses a zinc film on the surface of the steel plate, and zinc can play a sacrificial anode protection role on the steel, thereby protecting the steel. However, in a humid and harsh corrosive medium, the zinc of the galvanized steel will dissolve at a high rate, so that white-gray zinc oxide appears on the surface, which in turn causes corrosion of the steel. The present invention further uses a protective film to further protect the galvanized steel plate. The silane film has the advantages of being non-toxic and harmless, simple to operate, having a wide range of raw materials, and low cost, and has an excellent anti-corrosion effect. The organic-inorganic composite film is prepared by compounding with the prepared rare earth nanoparticles and rare earth salts. The deposition of La / Sc oxide nanoparticles and cerium salts can not only improve the barrier properties of the silane coating, but also be used to store lanthanum ions, scandium ions and cerium ions. When the coating is partially damaged, these metal ions are released from the nanoparticles and the silane coating, precipitated in the cathode area, hindering the cathode reaction, reducing corrosion, and playing a better protective effect. The three have a synergistic effect.
[0042] The composite silane coupling agent of the present invention is a mixture of KH580 with a mercapto group and KH792 with a diamino group, which can not only hydrolyze to form a silane film, but also stabilize metal ions through group chelation, thereby exerting a better stabilizing and corrosion reducing effect, and has a synergistic effect.
[0043] The 420 steel plate for laminating PCB boards prepared by the present invention has the advantages of large size (1300×1600 mm), thin thickness (less than 2 mm), high hardness, excellent flatness (less than 0.5 mm / m), large yield strength (1150-1500 MPa), high tensile strength (1500-1800 MPa), etc., and can be used to make PCB board pressing molding materials, and is mainly used in the PCB industry. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] In a specific embodiment, the 420 steel plate is purchased from Outokumpu Stainless Steel (China) Co., Ltd.
[0046] Preparation Example 1 Preparation of protective film liquid
[0047] The specific steps include:
[0048] S1. Silane hydrolysis: 10 parts by weight of a composite silane coupling agent was dissolved in 100 parts by weight of ethanol, 17 parts by weight of water was added, the pH value of the solution was adjusted to 8, heated to 40 ° C, stirred and hydrolyzed for 1 h to obtain a hydrolyzate;
[0049] The composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 3:7;
[0050] S2. La and Sc doping: 4 parts by weight of lanthanum nitrate and 2 parts by weight of scandium nitrate were added to 100 parts by weight of water, and 7 parts by weight of citric acid were added. The mixture was stirred at 35°C for 20 min, heated to 90°C to volatilize the solvent, calcined at 400°C for 1 h, and ball-milled for 2 h to obtain La / Sc oxide nanoparticles.
[0051] S3. Ce deposition: 3 parts by weight of La / Sc oxide nanoparticles prepared in step S2 are added to 100 parts by weight of the hydrolyzate prepared in step S1, and the mixture is stirred for 20 minutes. 4 parts by weight of cerium nitrate are added, and the mixture is stirred for 30 minutes to obtain a mixed solution.
[0052] S4. Preparation of protective film liquid: Add 10 parts by weight of 25wt% hydrogen peroxide to 100 parts by weight of the mixed solution obtained in step S3, stir and mix for 20 minutes to obtain a protective film liquid.
[0053] Preparation Example 2 Preparation of protective film liquid
[0054] The specific steps include:
[0055] S1. Silane hydrolysis: 12 parts by weight of a composite silane coupling agent was dissolved in 120 parts by weight of ethanol, 22 parts by weight of water were added, the pH value of the solution was adjusted to 9, heated to 50 ° C, stirred and hydrolyzed for 3h to obtain a hydrolyzate;
[0056] The composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 5:9;
[0057] S2. La and Sc doping: 6 parts by weight of lanthanum nitrate and 3 parts by weight of scandium nitrate were added to 100 parts by weight of water, and 10 parts by weight of citric acid were added. The mixture was stirred at 45°C for 40 min, heated to 90°C to volatilize the solvent, calcined at 500°C for 3 h, and ball-milled for 4 h to obtain La / Sc oxide nanoparticles.
[0058] S3. Ce deposition: 5 parts by weight of La / Sc oxide nanoparticles prepared in step S2 are added to 100 parts by weight of the hydrolyzate prepared in step S1, and the mixture is stirred for 20 minutes. 6 parts by weight of cerium nitrate are added, and the mixture is stirred for 40 minutes to obtain a mixed solution.
[0059] S4. Preparation of protective film liquid: To 100 parts by weight of the mixed solution obtained in step S3, 15 parts by weight of 30 wt% hydrogen peroxide were added, and the mixture was stirred for 20 minutes to obtain a protective film liquid.
[0060] Preparation Example 3 Preparation of protective film liquid
[0061] The specific steps include:
[0062] S1. Silane hydrolysis: 11 parts by weight of a composite silane coupling agent was dissolved in 110 parts by weight of ethanol, 20 parts by weight of water were added, the pH value of the solution was adjusted to 8.5, heated to 45 ° C, stirred and hydrolyzed for 2h to obtain a hydrolyzate;
[0063] The composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 4:8;
[0064] S2. La and Sc doping: 5 parts by weight of lanthanum nitrate and 2.5 parts by weight of scandium nitrate were added to 100 parts by weight of water, and 8.5 parts by weight of citric acid were added. The mixture was stirred at 40°C for 30 minutes, heated to 90°C to volatilize the solvent, calcined at 450°C for 2 hours, and ball-milled for 3 hours to obtain La / Sc oxide nanoparticles.
[0065] S3. Ce deposition: 4 parts by weight of La / Sc oxide nanoparticles prepared in step S2 are added to 100 parts by weight of the hydrolyzate prepared in step S1, and the mixture is stirred for 20 minutes. 5 parts by weight of cerium nitrate are added, and the mixture is stirred for 35 minutes to obtain a mixed solution.
[0066] S4. Preparation of protective film liquid: To 100 parts by weight of the mixed solution obtained in step S3, 12 parts by weight of 27 wt% hydrogen peroxide were added, and the mixture was stirred for 20 minutes to obtain a protective film liquid.
[0067] Preparation Example 4
[0068] Compared with Preparation Example 3, the difference is that the composite silane coupling agent is a single KH580.
[0069] Preparation Example 5
[0070] Compared with Preparation Example 3, the difference is that the composite silane coupling agent is a single KH792.
[0071] Comparative Preparation Example 1
[0072] Compared with Preparation Example 3, the difference is that lanthanum nitrate is not added in step S2.
[0073] The details are as follows:
[0074] S1. Silane hydrolysis: 11 parts by weight of a composite silane coupling agent was dissolved in 110 parts by weight of ethanol, 20 parts by weight of water were added, the pH value of the solution was adjusted to 8.5, heated to 45 ° C, stirred and hydrolyzed for 2h to obtain a hydrolyzate;
[0075] The composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 4:8;
[0076] S2. Sc doping: 7.5 parts by weight of scandium nitrate were added to 100 parts by weight of water, and 8.5 parts by weight of citric acid were added, and the mixture was stirred at 40°C for 30 min, and then heated to 90°C to volatilize the solvent, and then calcined at 450°C for 2 h, and ball-milled for 3 h to obtain Sc oxide nanoparticles;
[0077] S3. Ce deposition: 4 parts by weight of Sc oxide nanoparticles prepared in step S2 are added to 100 parts by weight of the hydrolyzate prepared in step S1, and the mixture is stirred for 20 minutes. 5 parts by weight of cerium nitrate are added, and the mixture is stirred for 35 minutes to obtain a mixed solution.
[0078] S4. Preparation of protective film liquid: To 100 parts by weight of the mixed solution obtained in step S3, 12 parts by weight of 27 wt% hydrogen peroxide were added, and the mixture was stirred for 20 minutes to obtain a protective film liquid.
[0079] Comparative Preparation Example 2
[0080] Compared with Preparation Example 3, the difference is that scandium nitrate is not added in step S2.
[0081] The details are as follows:
[0082] S1. Silane hydrolysis: 11 parts by weight of a composite silane coupling agent was dissolved in 110 parts by weight of ethanol, 20 parts by weight of water were added, the pH value of the solution was adjusted to 8.5, heated to 45 ° C, stirred and hydrolyzed for 2h to obtain a hydrolyzate;
[0083] The composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 4:8;
[0084] S2. La doping: 7.5 parts by weight of lanthanum nitrate was added to 100 parts by weight of water, and 8.5 parts by weight of citric acid was added, and the mixture was stirred at 40°C for 30 minutes, and then heated to 90°C to volatilize the solvent, and then calcined at 450°C for 2 hours, and ball-milled for 3 hours to obtain La oxide nanoparticles;
[0085] S3. Ce deposition: 4 parts by weight of La oxide nanoparticles prepared in step S2 are added to 100 parts by weight of the hydrolyzate prepared in step S1, and the mixture is stirred for 20 minutes. 5 parts by weight of cerium nitrate are added, and the mixture is stirred for 35 minutes to obtain a mixed solution.
[0086] S4. Preparation of protective film liquid: To 100 parts by weight of the mixed solution obtained in step S3, 12 parts by weight of 27 wt% hydrogen peroxide were added, and the mixture was stirred for 20 minutes to obtain a protective film liquid.
[0087] Comparative Preparation Example 3
[0088] Compared with Preparation Example 3, the difference is that step S2 is not performed.
[0089] The details are as follows:
[0090] S1. Silane hydrolysis: 11 parts by weight of a composite silane coupling agent was dissolved in 110 parts by weight of ethanol, 20 parts by weight of water were added, the pH value of the solution was adjusted to 8.5, heated to 45 ° C, stirred and hydrolyzed for 2h to obtain a hydrolyzate;
[0091] The composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 4:8;
[0092] S2. Ce deposition: 9 parts by weight of cerium nitrate were added to 100 parts by weight of the hydrolyzate obtained in step S1, and the mixture was stirred for 35 minutes to obtain a mixed solution;
[0093] S3. Preparation of protective film liquid: To 100 parts by weight of the mixed solution obtained in step S2, 12 parts by weight of 27 wt% hydrogen peroxide were added, and the mixture was stirred for 20 minutes to obtain a protective film liquid.
[0094] Comparative Preparation Example 4
[0095] Compared with Preparation Example 3, the difference is that step S3 is not performed.
[0096] The details are as follows:
[0097] S1. Silane hydrolysis: 11 parts by weight of a composite silane coupling agent was dissolved in 110 parts by weight of ethanol, 20 parts by weight of water were added, the pH value of the solution was adjusted to 8.5, heated to 45 ° C, stirred and hydrolyzed for 2h to obtain a hydrolyzate;
[0098] The composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 4:8;
[0099] S2. La and Sc doping: 5 parts by weight of lanthanum nitrate and 2.5 parts by weight of scandium nitrate were added to 100 parts by weight of water, and 8.5 parts by weight of citric acid were added. The mixture was stirred at 40°C for 30 minutes, heated to 90°C to volatilize the solvent, calcined at 450°C for 2 hours, and ball-milled for 3 hours to obtain La / Sc oxide nanoparticles.
[0100] S3. Preparation of protective film liquid: 4 parts by weight of La / Sc oxide nanoparticles prepared in step S2 were added to 100 parts by weight of the hydrolyzate prepared in step S1, 12 parts by weight of 27wt% hydrogen peroxide were added, and the mixture was stirred for 20 minutes to obtain a protective film liquid.
[0101] Example 1
[0102] This embodiment provides a method for preparing a 420 steel plate for laminating a PCB board, comprising the following steps:
[0103] (1) The surface of the 420 steel plate was washed with 1 mol / L hydrochloric acid to remove the oxide film;
[0104] (2) quenching the steel plate treated in step (1) at a temperature of 900° C. for a quenching holding time of 60 min, and then cooling in stages: cooling in a salt (sodium chloride) bath between the quenching temperature and 650° C., cooling in a silicone oil bath between 300° C. and 650° C., and cooling in water between 300° C. and room temperature;
[0105] (3) normalizing the steel plate after the treatment in step (2), wherein the normalizing temperature is 890° C. and the holding time is 40 min, and then performing a primary tempering treatment, cooling naturally to room temperature, and then performing a secondary tempering treatment, cooling naturally to room temperature;
[0106] The temperature of the first tempering treatment is 550°C, the holding time is 100 min, the second tempering treatment is 670°C, the time is 120 min, and the heating rate of the tempering treatment is 3°C / min;
[0107] (4) cold rolling the steel plate treated in step (3) at a reduction ratio of 50% and a cold rolling temperature of 380° C. to a thickness of less than 2 mm;
[0108] (5) The steel plate treated in step (4) was immersed in a zinc solution at 454° C., taken out, cooled to room temperature, dried at 100° C. for 1 h, immersed in the protective film solution prepared in Preparation Example 1, heated to 70° C., immersed for 0.5 h, taken out, and dried at 100° C. for 1 h;
[0109] (6) The steel plate treated in step (5) is continuously annealed in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled at 770°C, and the burn-through time per millimeter is controlled at 30s;
[0110] (7) The steel plate treated in step (6) is subjected to straightening by tension with a reduction of 0.1 mm and an elongation of 0.3% to obtain a 420 steel plate for laminating PCB boards.
[0111] Example 2
[0112] This embodiment provides a method for preparing a 420 steel plate for laminating a PCB board, comprising the following steps:
[0113] (1) The surface of the 420 steel plate was washed with 2 mol / L sulfuric acid to remove the oxide film;
[0114] (2) quenching the steel plate treated in step (1) at a temperature of 910° C. for a quenching holding time of 70 min, and then cooling in stages: cooling in a salt (sodium chloride or potassium chloride) bath between the quenching temperature and 650° C., cooling in silicone oil between 300° C. and 650° C., and cooling in water between 300° C. and room temperature;
[0115] (3) normalizing the steel plate after the treatment in step (2) at a temperature of 900° C. for a holding time of 50 min, then performing a primary tempering treatment, cooling naturally to room temperature, then performing a secondary tempering treatment, and cooling naturally to room temperature;
[0116] The temperature of the first tempering treatment is 600°C, the holding time is 120min, the second tempering treatment is 690°C, the time is 130min, and the heating rate of the tempering treatment is 5°C / min;
[0117] (4) cold rolling the steel plate treated in step (3) at a reduction ratio of 60% and a cold rolling temperature of 400° C. to a thickness of less than 2 mm;
[0118] (5) The steel plate treated in step (4) was immersed in a zinc solution at 459° C., taken out, cooled to room temperature, dried at 100° C. for 1 h, immersed in the protective film solution prepared in Preparation Example 2, heated to 80° C., immersed for 1 h, taken out, and dried at 100° C. for 1 h;
[0119] (6) The steel plate treated in step (5) is continuously annealed in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled at 800°C, and the burn-through time per millimeter is controlled at 40s;
[0120] (7) The steel plate treated in step (6) is subjected to straightening by tension with a reduction of 0.15 mm and an elongation of 0.5% to obtain a 420 steel plate for laminating PCB boards.
[0121] Example 3
[0122] This embodiment provides a method for preparing a 420 steel plate for laminating a PCB board, comprising the following steps:
[0123] (1) The surface of the 420 steel plate was washed with 1.5 mol / L hydrochloric acid to remove the oxide film;
[0124] (2) quenching the steel plate treated in step (1) at a temperature of 905° C. for a quenching holding time of 65 min, and then cooling in stages: cooling in a salt (sodium chloride or potassium chloride) bath between the quenching temperature and 650° C., cooling in a silicone oil bath between 300° C. and 650° C., and cooling in water between 300° C. and room temperature;
[0125] (3) normalizing the steel plate after the treatment in step (2), wherein the normalizing temperature is 895° C. and the holding time is 45 min, and then performing a primary tempering treatment, cooling naturally to room temperature, and then performing a secondary tempering treatment, cooling naturally to room temperature;
[0126] The temperature of the first tempering treatment is 570°C, the holding time is 110 min, the second tempering treatment is 680°C, the time is 125 min, and the heating rate of the tempering treatment is 4°C / min;
[0127] (4) cold rolling the steel plate treated in step (3) at a reduction ratio of 55% and a cold rolling temperature of 390° C. to a thickness of less than 2 mm;
[0128] (5) The steel plate treated in step (4) was immersed in a zinc solution at 457° C., taken out, cooled to room temperature, dried at 100° C. for 1 h, immersed in the protective film solution prepared in Preparation Example 3, heated to 75° C., immersed for 1 h, taken out, and dried at 100° C. for 1 h;
[0129] (6) The steel plate treated in step (5) is continuously annealed in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled at 785°C, and the burn-through time per millimeter is controlled at 35s;
[0130] (7) The steel plate treated in step (6) is subjected to straightening by tension with a reduction of 0.12 mm and an elongation of 0.4% to obtain a 420 steel plate for laminating PCB boards.
[0131] Example 4
[0132] Compared with Example 3, the difference is that the protective film liquid is prepared by Preparation Example 4.
[0133] Example 5
[0134] Compared with Example 3, the difference is that the protective film liquid is prepared by Preparation Example 5.
[0135] Comparative Example 1
[0136] Compared with Example 3, the difference is that the protective film liquid is prepared by Comparative Preparation Example 1.
[0137] Comparative Example 2
[0138] Compared with Example 3, the difference is that the protective film liquid is prepared by Comparative Preparation Example 2.
[0139] Comparative Example 3
[0140] Compared with Example 3, the difference is that the protective film liquid is prepared by Comparative Preparation Example 3.
[0141] Comparative Example 4
[0142] Compared with Example 3, the difference is that the protective film liquid is prepared by Comparative Preparation Example 4.
[0143] Comparative Example 5
[0144] Compared with Example 3, the difference is that no protective film liquid treatment is performed.
[0145] The details are as follows:
[0146] (1) The surface of the 420 steel plate was washed with 1.5 mol / L hydrochloric acid to remove the oxide film;
[0147] (2) quenching the steel plate treated in step (1) at a temperature of 905° C. for a quenching holding time of 65 min, and then cooling in stages: cooling in a salt (sodium chloride or potassium chloride) bath between the quenching temperature and 650° C., cooling in a silicone oil bath between 300° C. and 650° C., and cooling in water between 300° C. and room temperature;
[0148] (3) normalizing the steel plate after the treatment in step (2), wherein the normalizing temperature is 895° C. and the holding time is 45 min, and then performing a primary tempering treatment, cooling naturally to room temperature, and then performing a secondary tempering treatment, cooling naturally to room temperature;
[0149] The temperature of the first tempering treatment is 570°C, the holding time is 110 min, the second tempering treatment is 680°C, the time is 125 min, and the heating rate of the tempering treatment is 4°C / min;
[0150] (4) cold rolling the steel plate treated in step (3) at a reduction ratio of 55% and a cold rolling temperature of 390° C. to a thickness of less than 2 mm;
[0151] (5) immersing the steel plate treated in step (4) in a zinc solution at 457° C., taking it out, cooling it to room temperature, and drying it at 100° C. for 1 h;
[0152] (6) The steel plate treated in step (5) is continuously annealed in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled at 785°C, and the burn-through time per millimeter is controlled at 35s;
[0153] (7) The steel plate treated in step (6) is subjected to straightening by tension with a reduction of 0.12 mm and an elongation of 0.4% to obtain a 420 steel plate for laminating PCB boards.
[0154] Comparative Example 6
[0155] Compared with Example 3, the difference is that in step (2), no staged cooling is performed, and water cooling is directly used to cool to room temperature.
[0156] The details are as follows:
[0157] (1) The surface of the 420 steel plate was washed with 1.5 mol / L hydrochloric acid to remove the oxide film;
[0158] (2) quenching the steel plate treated in step (1) at a temperature of 905° C. for a quenching holding time of 65 min, and then water cooling to room temperature;
[0159] (3) normalizing the steel plate after the treatment in step (2), wherein the normalizing temperature is 895° C. and the holding time is 45 min, and then performing a primary tempering treatment, cooling naturally to room temperature, and then performing a secondary tempering treatment, cooling naturally to room temperature;
[0160] The temperature of the first tempering treatment is 570°C, the holding time is 110 min, the second tempering treatment is 680°C, the time is 125 min, and the heating rate of the tempering treatment is 4°C / min;
[0161] (4) cold rolling the steel plate treated in step (3) at a reduction ratio of 55% and a cold rolling temperature of 390° C. to a thickness of less than 2 mm;
[0162] (5) The steel plate treated in step (4) was immersed in a zinc solution at 457° C., taken out, cooled to room temperature, dried at 100° C. for 1 h, immersed in the protective film solution prepared in Preparation Example 3, heated to 75° C., immersed for 1 h, taken out, and dried at 100° C. for 1 h;
[0163] (6) The steel plate treated in step (5) is continuously annealed in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled at 785°C, and the burn-through time per millimeter is controlled at 35s;
[0164] (7) The steel plate treated in step (6) is subjected to straightening by tension with a reduction of 0.12 mm and an elongation of 0.4% to obtain a 420 steel plate for laminating PCB boards.
[0165] Comparative Example 7
[0166] Compared with Example 3, the difference is that only one tempering treatment is used in step (3).
[0167] The details are as follows:
[0168] (1) The surface of the 420 steel plate was washed with 1.5 mol / L hydrochloric acid to remove the oxide film;
[0169] (2) quenching the steel plate treated in step (1) at a temperature of 905° C. for a quenching holding time of 65 min, and then cooling in stages: cooling in a salt (sodium chloride or potassium chloride) bath between the quenching temperature and 650° C., cooling in a silicone oil bath between 300° C. and 650° C., and cooling in water between 300° C. and room temperature;
[0170] (3) normalizing the steel plate after the treatment in step (2), wherein the normalizing temperature is 895° C. and the holding time is 45 min, and then tempering is performed and naturally cooled to room temperature;
[0171] The tempering treatment temperature is 570°C, the holding time is 110min, and the tempering treatment heating rate is 4°C / min;
[0172] (4) cold rolling the steel plate treated in step (3) at a reduction ratio of 55% and a cold rolling temperature of 390° C. to a thickness of less than 2 mm;
[0173] (5) The steel plate treated in step (4) was immersed in a zinc solution at 457° C., taken out, cooled to room temperature, dried at 100° C. for 1 h, immersed in the protective film solution prepared in Preparation Example 3, heated to 75° C., immersed for 1 h, taken out, and dried at 100° C. for 1 h;
[0174] (6) The steel plate treated in step (5) is continuously annealed in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled at 785°C, and the burn-through time per millimeter is controlled at 35s;
[0175] (7) The steel plate treated in step (6) is subjected to straightening by tension with a reduction of 0.12 mm and an elongation of 0.4% to obtain a 420 steel plate for laminating PCB boards.
[0176] Comparative Example 8
[0177] Compared with Example 3, the difference is that only secondary tempering treatment is used in step (3).
[0178] The details are as follows:
[0179] (1) The surface of the 420 steel plate was washed with 1.5 mol / L hydrochloric acid to remove the oxide film;
[0180] (2) quenching the steel plate treated in step (1) at a temperature of 905° C. for a quenching holding time of 65 min, and then cooling in stages: cooling in a salt (sodium chloride or potassium chloride) bath between the quenching temperature and 650° C., cooling in a silicone oil bath between 300° C. and 650° C., and cooling in water between 300° C. and room temperature;
[0181] (3) normalizing the steel plate treated in step (2) at a temperature of 895° C. for a holding time of 45 min, and then tempering the steel plate and naturally cooling the steel plate to room temperature;
[0182] The tempering treatment is performed at 680°C for 125 minutes, and the heating rate of the tempering treatment is 4°C / min;
[0183] (4) cold rolling the steel plate treated in step (3) at a reduction ratio of 55% and a cold rolling temperature of 390° C. to a thickness of less than 2 mm;
[0184] (5) The steel plate treated in step (4) was immersed in a zinc solution at 457° C., taken out, cooled to room temperature, dried at 100° C. for 1 h, immersed in the protective film solution prepared in Preparation Example 3, heated to 75° C., immersed for 1 h, taken out, and dried at 100° C. for 1 h;
[0185] (6) The steel plate treated in step (5) is continuously annealed in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled at 785°C, and the burn-through time per millimeter is controlled at 35s;
[0186] (7) The steel plate treated in step (6) is subjected to straightening by tension with a reduction of 0.12 mm and an elongation of 0.4% to obtain a 420 steel plate for laminating PCB boards.
[0187] Comparative Example 9
[0188] Compared with Example 3, the difference is that no tempering treatment is performed in step (3).
[0189] The details are as follows:
[0190] (1) The surface of the 420 steel plate was washed with 1.5 mol / L hydrochloric acid to remove the oxide film;
[0191] (2) quenching the steel plate treated in step (1) at a temperature of 905° C. for a quenching holding time of 65 min, and then cooling in stages: cooling in a salt (sodium chloride or potassium chloride) bath between the quenching temperature and 650° C., cooling in a silicone oil bath between 300° C. and 650° C., and cooling in water between 300° C. and room temperature;
[0192] (3) normalizing the steel plate treated in step (2), wherein the normalizing temperature is 895° C., the holding time is 45 min, and the steel plate is naturally cooled to room temperature;
[0193] (4) cold rolling the steel plate treated in step (3) at a reduction ratio of 55% and a cold rolling temperature of 390° C. to a thickness of less than 2 mm;
[0194] (5) The steel plate treated in step (4) was immersed in a zinc solution at 457° C., taken out, cooled to room temperature, dried at 100° C. for 1 h, immersed in the protective film solution prepared in Preparation Example 3, heated to 75° C., immersed for 1 h, taken out, and dried at 100° C. for 1 h;
[0195] (6) The steel plate treated in step (5) is continuously annealed in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled at 785°C, and the burn-through time per millimeter is controlled at 35s;
[0196] (7) The steel plate treated in step (6) is subjected to straightening by tension with a reduction of 0.12 mm and an elongation of 0.4% to obtain a 420 steel plate for laminating PCB boards.
[0197] Comparative Example 10
[0198] Compared with Example 3, the difference is that step (3) is not performed.
[0199] The details are as follows:
[0200] (1) The surface of the 420 steel plate was washed with 1.5 mol / L hydrochloric acid to remove the oxide film;
[0201] (2) quenching the steel plate treated in step (1) at a temperature of 905° C. for a quenching holding time of 65 min, and then cooling in stages: cooling in a salt (sodium chloride or potassium chloride) bath between the quenching temperature and 650° C., cooling in a silicone oil bath between 300° C. and 650° C., and cooling in water between 300° C. and room temperature;
[0202] (3) cold rolling the steel plate treated in step (2) at a reduction ratio of 55% and a cold rolling temperature of 390° C. to a thickness of less than 2 mm;
[0203] (4) The steel plate treated in step (3) was immersed in a zinc solution at 457° C., taken out, cooled to room temperature, dried at 100° C. for 1 h, immersed in the protective film solution prepared in Preparation Example 3, heated to 75° C., immersed for 1 h, taken out, and dried at 100° C. for 1 h;
[0204] (5) The steel plate treated in step (4) is continuously annealed in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled at 785°C, and the burn-through time per millimeter is controlled at 35s;
[0205] (6) The steel plate treated in step (5) is subjected to straightening by tension with a reduction of 0.12 mm and an elongation of 0.4% to obtain a 420 steel plate for laminating PCB boards.
[0206] Test Example 1
[0207] The 420 steel plates for laminated PCB boards prepared in Examples 1-5 of the present invention and Comparative Examples 1-10 were subjected to mechanical property tests.
[0208] According to GB / T 2975-1998 "Sampling location and specimen preparation for mechanical properties test of steel and steel products", the steel plate is sampled. The sampling location is 1 / 4 of the width direction of the middle part of the steel plate.
[0209] The tensile test was carried out in accordance with GB / T 228.1-2010 “Tensile test of metallic materials - Part 1: Test method at room temperature”, and the tensile specimen was in the longitudinal direction.
[0210] The impact test was carried out on a ZBC2452N-2 pendulum impact tester with a cross-sectional size of 10 mm*10 mm and a V-notch depth of 2 mm. The average value of three specimens was taken.
[0211] The results are shown in Table 1.
[0212] Table 1
[0213]
[0214]
[0215] It can be seen from the above table that the 420 steel plates for laminated PCB boards prepared in Examples 1-3 of the present invention have good mechanical properties.
[0216] Test Example 2
[0217] A CHI660D electrochemical workstation was used to perform corrosion resistance tests on the 420 steel plates for laminated PCB boards prepared in Examples 1-5 and Comparative Examples 1-10 using a three-electrode system.
[0218] The working electrode is a passivation sample made of 420 steel plate used for laminating PCB boards, with an effective area of 1cm 2 The auxiliary electrode is a platinum sheet, and the reference electrode is a saturated calomel electrode, which is connected to the test system using a salt bridge. The passivated sample is immersed in a 3.5% NaCl solution for 30 minutes, and the corrosion electrochemical parameters are tested after the open circuit potential stabilizes. The AC impedance frequency range is 10 5 -10 -2 Hz, AC voltage amplitude of 5mV, tested at open circuit potential. The scanning potential of the polarization curve test relative to the open circuit potential is ±250mV, and the scanning rate is 1mV / s.
[0219] The results are shown in Table 2.
[0220] Table 2
[0221]
[0222]
[0223] It can be seen from the above table that the 420 steel plates for laminated PCB boards prepared in Examples 1-3 of the present invention have good corrosion resistance.
[0224] Test Example 3
[0225] The 420 steel plates for laminated PCB boards prepared in Examples 1-5 of the present invention and Comparative Examples 1-10 were subjected to performance tests.
[0226] The results are shown in Table 3.
[0227] Table 3
[0228] Group Thickness deviation(mm) Vickers hardness (HV) Straightness(mm / m) Surface roughness(μm) Example 1 0.02 365 0.02 0.09 Example 2 0.02 363 0.03 0.10 Example 3 0.01 369 0.02 0.07 Example 4 0.03 351 0.04 0.13 Example 5 0.03 354 0.05 0.14 Comparative Example 1 0.02 349 0.05 0.12 Comparative Example 2 0.03 346 0.06 0.13 Comparative Example 3 0.04 341 0.08 0.15 Comparative Example 4 0.03 344 0.07 0.16 Comparative Example 5 0.05 335 0.10 0.21 Comparative Example 6 0.06 322 0.14 0.25 Comparative Example 7 0.05 329 0.11 0.20 Comparative Example 8 0.05 330 0.12 0.18 Comparative Example 9 0.07 308 0.15 0.24 Comparative Example 10 0.09 295 0.18 0.29
[0229] It can be seen from the above table that the 420 steel plates for laminated PCB boards prepared in Examples 1-3 of the present invention have better comprehensive properties.
[0230] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a 420 steel plate for laminating a PCB board, characterized in that: The following steps are involved: (1) The 420 steel plate is subjected to surface pickling treatment to remove the oxide film; (2) quenching the steel plate treated in step (1) and then cooling it in stages; the quenching temperature is 900-910°C, the quenching holding time is 60-70 min, and the staged cooling is salt bath cooling between the quenching temperature and 650°C, oil cooling between 300°C and 650°C, and water cooling between 300°C and room temperature; (3) normalizing the steel plate treated in step (2), then performing a primary tempering treatment, cooling naturally to room temperature, then performing a secondary tempering treatment, and cooling naturally to room temperature; the normalizing temperature is 890-900°C, and the holding time is 40-50 min; the primary tempering temperature is 550-600°C, and the holding time is 100-120 min; the secondary tempering temperature is 670-690°C, and the holding time is 120-130 min; and the heating rate of the tempering treatment is 3-5°C / min; (4) cold rolling the steel plate treated in step (3) to a thickness of less than 2 mm; the cold rolling adopts a reduction rate of 50-60% and a cold rolling temperature of 380-400° C.; (5) immersing the steel plate treated in step (4) in a zinc solution, taking it out, cooling it to room temperature, drying it, immersing it in a protective film solution, heating it, taking it out, and drying it; the temperature of the zinc solution is 454-459° C., the protective film solution is a H2O2 / silane hydrolyzate solution mixed with La / Sc oxide nanoparticles and cerium nitrate, the temperature of the heating treatment is 70-80° C., and the time is 0.5-1 h; The preparation method of the protective film liquid is as follows: S1. Silane hydrolysis: dissolving the composite silane coupling agent in ethanol, adding water, adjusting the pH value of the solution, heating and stirring to hydrolyze, and obtaining a hydrolyzate; the composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 3-5:7-9; S2. La and Sc doping: lanthanum nitrate and scandium nitrate are added to water, citric acid is added and stirred for reaction, the solvent is evaporated, calcined, and ball-milled to obtain La / Sc oxide nanoparticles; S3. Ce deposition: adding the La / Sc oxide nanoparticles obtained in step S2 to the hydrolyzate obtained in step S1, stirring and mixing evenly, adding cerium nitrate, stirring and reacting to obtain a mixed solution; S4 protective film liquid preparation: to the mixed solution obtained in step S3, add hydrogen peroxide, stir and mix well to obtain a protective film liquid; (6) performing final annealing on the steel plate treated in step (5); (7) The steel plate treated in step (6) is subjected to plate shape correction to obtain a 420 steel plate for laminating PCB boards.
2. The preparation method according to claim 1, characterized in that: The pickling acid in step (1) is 1-2 mol / L hydrochloric acid or sulfuric acid; the oil in step (2) is silicone oil, and the salt is sodium chloride or potassium chloride.
3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the composite silane coupling agent, ethanol and water is 10-12:100-120:17-22, the pH value of the adjusted solution is 8-9, the temperature of the heated and stirred hydrolysis is 40-50°C, and the time is 1-3h; in step S2, the mass ratio of lanthanum nitrate, scandium nitrate and citric acid is 4-6:2-3:7-10, the temperature of the stirred reaction is 35-45°C, the time is 20-40min, the temperature of the calcination is 400-500°C, the time is 1-3h, and the ball milling time is 2-4h.
4. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of La / Sc oxide nanoparticles, hydrolyzate and cerium nitrate is 3-5:100:4-6, and the stirring reaction time is 30-40 minutes; in step S4, the mass ratio of the mixed solution and hydrogen peroxide is 100:10-15, and the concentration of hydrogen peroxide is 25-30wt%.
5. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Silane hydrolysis: 10-12 parts by weight of a composite silane coupling agent is dissolved in 100-120 parts by weight of ethanol, 17-22 parts by weight of water are added, the pH value of the solution is adjusted to 8-9, heated to 40-50 ° C, stirred for hydrolysis for 1-3h to obtain a hydrolyzate; The composite silane coupling agent is a mixture of KH580 and KH792, with a mass ratio of 3-5:7-9; S2. La and Sc doping: 4-6 parts by weight of lanthanum nitrate and 2-3 parts by weight of scandium nitrate are added to 100 parts by weight of water, and 7-10 parts by weight of citric acid are added. The mixture is stirred at 35-45° C. for 20-40 min, the solvent is evaporated, and the mixture is calcined at 400-500° C. for 1-3 h, and ball-milled for 2-4 h to obtain La / Sc oxide nanoparticles. S3. Ce deposition: add 3-5 parts by weight of La / Sc oxide nanoparticles obtained in step S2 to 100 parts by weight of the hydrolyzate obtained in step S1, stir and mix evenly, add 4-6 parts by weight of cerium nitrate, stir and react for 30-40 minutes to obtain a mixed solution; S4. Preparation of protective film liquid: Add 10-15 parts by weight of 25-30wt% hydrogen peroxide to 100 parts by weight of the mixed solution obtained in step S3, stir and mix evenly to obtain a protective film liquid.
6. The preparation method according to claim 1, characterized in that: The finished product annealing in step (6) is carried out by continuous annealing in a vertical furnace, the tension in the furnace is within 15N, the furnace temperature is controlled to be 770-800°C, and the burn-through time per millimeter is controlled to be 30-40s; in the plate shape correction in step (7), the drawing reduction is 0.1-0.15mm and the elongation is 0.3-0.5%.
7. A 420 steel plate for laminating PCB boards prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Alkaline silane rare-earth-doped treating agent for metal surface treatment and preparation method and application thereof
CN109722661A
Heat treatment process for prehardening 3Cr13 die steel medium plate
CN114196813A
Steel alloy for pressure plate sheet metal
DE2018938A1